HELICHRYSUM LONGIFOLIUM AND HELICHRYSUM PEDUNCULATUM: A COMPARATIVE ANALYSIS OF THEIR MEDICINAL USES, CHEMISTRY AND BIOLOGICAL ACTIVITIES: ETHNOPHARMACOLOGY OF HELICHRYSUM LONGIFOLIUM AND H. PEDUNCULATUM - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Helichrysum longifolium and Helichrysum pedunculatum have a long history of medicinal use, particularly managing wounds acquired during male circumcision rites in South Africa. There is a need to evaluate the existence of any correlation between the ethnomedicinal applications, the phytochemistry and pharmacological properties of the species. Therefore, in this review, analyses of the botanical, medicinal, and chemical and biological activities of H. longifolium and H. pedunculatum are presented as well as exploring the potential of the two species as important sources of health and pharmaceutical products. Information on the botany, medicinal uses, and phytochemistry and biological activities of H. longifolium and H. pedunculatum was assembled from several internet sources which included Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, PubMed, SciFinder, and BMC. Additional information was sourced from journal articles, scientific reports, theses, books, and book chapters obtained from the University library. This study showed that alkaloids, flavonoids, linoleic acid, oleic acid, phenol, proanthocyanidin, saponins, and tannins have been identified from the leaves of H. longifolium and H. pedunculatum. The pharmacological research showed that H. longifolium and H. pedunculatum extracts and compounds isolated from the species have antibacterial, antifungal, anti-inflammatory, antioxidant, antiplasmodial, antiprotozoal, and cytotoxicity activities. For local communities to use H. longifolium and H. pedunculatum extracts with confidence as herbal medicines, there is a need for extensive phytochemical and pharmacological studies. Further research is required to establish the safety profiles of different H. longifolium and H. pedunculatum preparations.